(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
Though early marriage is a problem in all communities in Nepal, few studies have looked specifically at very remote Dalit communities. This research explores the impact of early marriage on reproductive health and the use of healthcare services in the Sarki Dalit community of Baghchaur Municipality ward no. 2, Salyan District. Using an explanatory sequential design of mixed methods, we began with a census survey of every married woman with children, of which there were 167, and subsequently three additional qualitative in-depth interviews. The results showed that the problem is much more severe than anticipated: the median age of marriage is 16, and 42.5% of women were pregnant before age 15. Contact with the health system for maternal care was nearly nonexistent: 98.2% of women home-delivered their last baby, and 44.3% of women had no ANC. Binary logistic regression showed maternal literacy as the strongest predictor of receiving any ANC, with the odds of 4.6 (95% 2.15- 9.88, p<.001). The qualitative data showed that the active avoidance of maternal care was caused by a combination of deep-seated distrust in the health system, geographical remoteness, and poverty. As a result, the responding health system failed to meet its expected targets. The absence of national programs and the systemic abandonment that this community has received highlight the need for a multi-sectoral association.